Go together, to go further! Reply to "Human–water research: discussion of 'Guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants'". Issue 14 (26th October 2022) - Höllermann, Britta; Rangecroft, Sally; Rohse, Melanie; Banks, Eddie W.; Day, Rosie; Di Baldassarre, Giuliano; Frommen, Theresa; Hayashi, Yasunori; Lebek, Karen; Mondino, Elena; Rusca, Maria; Wens, Marthe; et al.
ABSTRACT: In this reply to Thaler, we take the opportunity to explore two main aspects of his piece to continue the discussion: (1) the integration of data from the social and natural sciences, and (2) the importance of transdisciplinary research. We agree, and highlight that necessary learning, reflections and participation processes are time-intensive for researchers, practitioners and participants. We believe that these discussion pieces are important for informing, engaging, and debating challenges and practices, providing continued opportunities to learn from one another, enabling new forms of research and collaborations to flourish.